1980
DOI: 10.1007/bf00716371
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to hexachlorocyclohexane

Abstract: In a lindane (gamma-hexachlorocyclohexane = gamma-benzenehexachloride)-producing factor 57 workers were studied with regard to their blood levels of the three hexachlorocyclohexane isomers: alpha-, beta-, and gamma-HCH. The TLV-TWA (MAK value 1979) for gamma-HCH of 0.5 mg/m3 was not exceeded at any of the workplaces where HCH is synthesized and purified to lindane. Additionally, in some of the workers samples of s.c. adipose tissue were taken for determination of HCH-isomer content. An external group of 20 cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(10 citation statements)
references
References 9 publications
1
7
1
Order By: Relevance
“…The concentration of lindane used in the present study is about 100-fold higher than serum concentrations observed in 700 GLUTATHIONE MODULATION AND GAP JUNCTIONS occupationally exposed human populations (Baumann et al, 1980) and is significantly higher than concentrations reported in human blood samples of populations lacking known exposure to lindane (Kutz et al, 1991). Nonetheless, because lindane induces a sustained inhibition of myometrial gap junction communication at nanomolar concentrations (Loch-Caruso et al, 2003), an improved understanding of lindane effects on gap junctions may have relevance for understanding potential health risks.…”
Section: Loch-caruso Et Alcontrasting
confidence: 54%
“…The concentration of lindane used in the present study is about 100-fold higher than serum concentrations observed in 700 GLUTATHIONE MODULATION AND GAP JUNCTIONS occupationally exposed human populations (Baumann et al, 1980) and is significantly higher than concentrations reported in human blood samples of populations lacking known exposure to lindane (Kutz et al, 1991). Nonetheless, because lindane induces a sustained inhibition of myometrial gap junction communication at nanomolar concentrations (Loch-Caruso et al, 2003), an improved understanding of lindane effects on gap junctions may have relevance for understanding potential health risks.…”
Section: Loch-caruso Et Alcontrasting
confidence: 54%
“…The β-isomer is generally considered the most persistent and metabolically inactive, with a BCF of 2.9 in various aquatic species and 527 in human fat (see Table 1). For example, in workers involved in the production of lindane, concentrations of β-HCH (46 mg/kg lipid) were 8 and 15 times the concentrations of Rand γ-HCH, respectively (46). Likewise, average lipid β-HCH concentrations in 20 Pakistani citizens (average, 2.4 mg/kg; range, 0.14-21 mg/kg) were 8 and 80 times higher than Rand γ-HCH (47).…”
Section: Human Hch Residue Concentrations and Exposure Routesmentioning
confidence: 97%
“…In workers engaged in the production and formulation of γ-HCH, mean plasma levels ranged from 16–57 µg/L [ 34 ]. In another γ-HCH-producing facility, γ-HCH air levels of 0.004–0.15 mg/m 3 were associated with serum levels of 5–188 µg/L in exposed workers of [ 35 ]. The high serum γ-HCH concentrations in our study in both controls (2.8 ± 0.49 μg/L) and T2DM patients (7.3 ± 0.84) indicate a recent or current exposure to γ-HCH either through diet, drinking water or polluted air.…”
Section: Resultsmentioning
confidence: 99%